Pembelajaran Menulis Puisi Berbantuan Media Gambar - Lina, Sepini Pitria; Atmazaki, Atmazaki; Abdurahman, Abdurahman (Universitas Negeri Padang, 2013)
The purpose of this research is to describe the process of students ability development at class VII-1 SMP Negeri 4 Sutera in writing poetry by using pictures media. This research is a kind of classroom action research which using descriptive methods. The population of this research is all students of class VII-1 SMP 4 Sutera. The data was collected in the form of tests and non-tests. The test is used to collect the data of students’ capability to write poetry, while non-test is used to collect the data of the media pictures application in poetry writing. From the results of this research, it can be concluded that learning to write poetry by using pictures media can improve the ability of students SMP 4 Sutera class VII-1 in writing poetry.